BSP implementation of European S3 - level evidence-based treatment guidelines for stage I-III periodontitis in UK clinical practice. (March 2021) - West, Nicola; Chapple, Iain; Claydon, Nick; D'Aiuto, Francesco; Donos, Nikos; Ide, Mark; Needleman, Ian; Kebschull, Moritz; ,
Abstract: Objectives: To adapt the supranational European Federation for Periodontology (EFP) S3-Level Clinical Practice Guideline for treatment of periodontitis (stage I-III) to a UK healthcare environment, taking into account the views of a broad range of stakeholders, and patients. Sources: This UK version is based on the supranational EFP guideline (Sanz et al., 2020) published in the Journal of Clinical Periodontology . The source guideline was developed using the S3-level methodology, which combined the assessment of formal evidence from 15 systematic reviews with a moderated consensus process of a representative group of stakeholders, and accounts for health equality, environmental factors and clinical effectiveness. It encompasses 62 clinical recommendations for the treatment of stage I–III periodontitis, based on a step-wise process mapped to the 2017 classification system. Methodology: The UK version was developed from the source guideline using a formal process called the GRADE ADOLOPMENT framework. This framework allows for the adoption (unmodified acceptance), adaptation (acceptance with modifications) and the de novo development of clinical recommendations. Using this framework and following the S3-process, the underlying systematic reviews were updated and a representative guideline group of 75 delegates from 17 stakeholder organisations was assembled into three working groups. Following the formal S3-process, all clinical recommendations were formally assessed for their applicability to the UK and adoloped accordingly. Results and conclusion: Using the ADOLOPMENT protocol, a UK version of the EFP S3-level clinical practice guideline was developed. This guideline delivers evidence- and consensus-based clinical recommendations of direct relevance to the dental community in the UK. Clinical significance: The aim of S3-level guidelines is to combine the evaluation of formal evidence, grading and synthesis with the clinical expertise of a broad range of stakeholders to form clinical recommendations. Herein, the first major international S3-level guideline in dentistry, the EFP guideline, was implemented for direct clinical applicability in the UK healthcare system.